A GDP, a HDI, a GNH és az OECD indikátorrendszere mint a fenntartható fejlődés indikátorai - Kotosz, Balázs (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
Sustainable development has been an important focus of current researches. To be able to test the theories, to develop goals, and to control their fulfillment we need measurement. The three main fields of sustainable development (economic, societal and ecological) have a series of indicators, but these indicators are not always applicable to achieve the above-mentioned goals. In the paper, we survey the requirements of the indicators absed on a wide-range literature, whether they are real and consistent ones, their possible weights in the three fields. After theoretical part, we analyze some wellknown measure to show that even these measures can be criticized. We conclude that none of the above mentioned measures are perfect ones, and sometimes the most criticized measures show better performance.